The Manipulation of Religion and The Legalization of Underage Marriages in Indonesia - Barkah, Qodariah; Cholidi, Cholidi; Rochmiyatun, Siti; Asmorowati, Sulikah; Fernando, Henky (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Cases of underage marriage have continued to increase, supported by religious law, and accepted by Indonesian Muslims. To analyze this phenomenon, this study is an empirical legal study using a qualitative descriptive approach. The data was obtained through observation, interviews, and a search for religious texts/arguments. The analysis was constructed to explain the relationship between the practice of early marriage and the use of the texts of the Qur'an and Hadith as the main sources in Islamic law. It shows that this exegetical approach has helped perpetuate the practice of underage marriage, as it not only promotes a partial and purely textual understanding of Islam's teachings regarding marriage but is also easily manipulated to promote certain views, as a form of religious manipulation of underage marriages. As a result, marriage is taught and understood from a purely doctrinal perspective, without considering the health and well-being of the married couple. Instead, this study recommends using an integrated approach that continuously strives to prevent the underage marriage, one capable of obtaining a comprehensive understanding that recognizes the interests of all stakeholders including underage couples. Only then can a comprehensive understanding of religious teachings and experiences be obtained